Ambient Assisted Living Italian Forum 2017 - Casiddu, Niccolò; Porfirione, Claudia; Monteriù, Andrea; Cavallo, Filippo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book documents the state of the art in the field of ambient assisted living (AAL), highlighting the impressive potential of novel methodologies and technologies to enhance well-being and promote active ageing. It covers a broad range of topics, with sections on technological sensors and platforms, social robotics for assistance, assistance and care applications, health and medical support methodologies and technologies, as well as the analysis, modelling and design of AAL services. The book comprises a selection of the best papers presented at the 8th Italian Forum on Ambient Assisted Living (ForitAAL 2017), which was held in Genoa, Italy, in June 2017 and brought together researchers, technology teams and professional associations, as well as representatives of the Italian regions and advisors to the Italian Ministry of Education, University and Research, with the goal of developing a consensus on how to improve provisions for the elderly and impaired. The respective contributions offer valuable insights into how the latest advances can help address the needs of the elderly and those with chronic health conditions. They also underscore the need for AAL to continue moving toward multidisciplinary integration, so as to embrace the various disciplines that place the user of services at the centre of the design process.
Keywords: Biomedical engineering; Control engineering; Robotics; Automation; Geriatrics; Aging; Biomedical Engineering and Bioengineering; Control, Robotics, Automation; Geriatrics; Ageing